Encyclopedia of Neuroscience - Binder, Marc D.; Hirokawa, Nobutaka; Windhorst, Uwe (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Unique in its breadth and detail, this encyclopedia offers a comprehensive and highly readable guide to a complex and fast-expanding field. The five-volume reference work gathers more than 10,000 entries, including in-depth essays by internationally known experts, and short keynotes explaining essential terms and phrases. In addition, expert editors contribute detailed introductory chapters to each of 43 topic fields ranging from the fundamentals of neuroscience to fascinating developments in the new, inter-disciplinary fields of Computational Neuroscience and Neurophilosophy. Some 1,000 multi-color illustrations enhance and expand the writings. This user-friendly reference will be indispensable to basic and clinical scientists and practitioners in academia, hospitals, private practice, and industry, as a source of reliable information on the structure and function of the nervous system. The Encyclopedia of Neuroscience opens the topic to health care professionals, students, teachers and informed laypersons who require relevant information on this rapidly evolving field.